2015
DOI: 10.3892/ol.2015.3953
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy with a novel porphyrin-based photosensitizer against human gastric cancer

Abstract: Abstract. The objective of the present study was to evaluate the effects of novel porphyrin-based photosensitizer meso-5-[ρ-diethylene triamine pentaacetic acid-a m i nophenyl]-10,15, 2 0 -t r iphenyl-p or phy r i n (DTP)-mediated photodynamic therapy (PDT) on the HGC27 and SNU-1 human gastric cancer cell lines. The absorption spectrum of DTP was analyzed using a microplate spectrophotometer. The HGC27 or SNU-1 cells were incubated with DTP and exposed to illumination by a 650-nm laser. The experiments were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In this review, PS mapping for tumor PDT can be roughly divided into three areas: Mitochondria[ 69 - 78 ], endoplasmic reticulum[ 12 , 68 , 79 - 82 ], and lysosomes[ 83 - 88 ]. These PSs can be roughly summarized into porphyrin-based photosensitizers, such as porphyrins[ 89 - 92 ], chlorins[ 80 , 93 , 94 ], phthalocyanines, and naphthalocyanines[ 95 - 99 ], and non-porphyrin-based photosensitizers, such as cyanine, methylene blue, Nile blue, rhodamine, triarylmethane, and acridine[ 68 , 100 - 105 ]. These PSs and their derivatives are summarized by category in Table 1 .…”
Section: Impact Of Ros From Pdt On Cscsmentioning
confidence: 99%
“…In this review, PS mapping for tumor PDT can be roughly divided into three areas: Mitochondria[ 69 - 78 ], endoplasmic reticulum[ 12 , 68 , 79 - 82 ], and lysosomes[ 83 - 88 ]. These PSs can be roughly summarized into porphyrin-based photosensitizers, such as porphyrins[ 89 - 92 ], chlorins[ 80 , 93 , 94 ], phthalocyanines, and naphthalocyanines[ 95 - 99 ], and non-porphyrin-based photosensitizers, such as cyanine, methylene blue, Nile blue, rhodamine, triarylmethane, and acridine[ 68 , 100 - 105 ]. These PSs and their derivatives are summarized by category in Table 1 .…”
Section: Impact Of Ros From Pdt On Cscsmentioning
confidence: 99%
“…NF-kB plays a critical role in the cellular response to different stimuli including stress, free radicals and ultraviolet irradiation and controls signaling pathways involved in cell survival. The TPPS-mediated apoptosis was reported also in human gastric cancer HGC27 and SNU-1 cells treated with a dose of 6.25 µM TPPS derivate and irradiation by a laser at 650 nm with 12 J/cm 2 [80].…”
Section: Discussionmentioning
confidence: 71%
“…Porphyrins accumulate intracellularly in endocytic vesicles, and are released into the cytosol after light exposure [ 30 ]. In this cellular compartment, porphyrins accumulate in crucial targeted sites, including mitochondrial or nucleus membranes and plasma membranes [ 13 , 41 , 53 ]. Our study confirmed these observations.…”
Section: Discussionmentioning
confidence: 99%